Paraquat Reduces the Female Fertility by Impairing the Oocyte Maturation in Mice - Sun, Yan-Li; Wang, Xue-Lin; Yang, Lei-Lei; Ge, Zhao-Jia; Zhao, Yong; Luo, Shi-Ming; Shen, Wei; Sun, Qing-Yuan; Yin, Shen (Frontiers in Cell and Developmental Biology, 2021)
Paraquat (PQ) is a widely used non-selective and oxidizing herbicide in farmland, orchards, flower nursery, and grassland. Overuse of PQ will accumulate in the body and affect the reproduction in mammals. In this study, we found that PQ could reduce the female fertility by oral administration for 21 days in mice. PQ exposure could impair the nuclear maturation by perturbing the spindle assembly and kinetochore–microtubule attachment to cause the misaligned chromosomes during meiosis. In the meantime, PQ exposure disturbed the mitochondrial distribution and enhanced the level of reactive oxygen species and early apoptosis, which thereby deteriorated the early embryo development. Also, PQ administration could cause some changes in epigenetic modifications such as the level of H3K9me2 and H3K27me3. Therefore, PQ administration reduces the female fertility by impairing the nuclear and cytoplasmic maturation of oocytes in mice.